Trends in Project Based Learning Models in Increase 6C Skills (Character, Citizenship, Critical Thinking, Creative, Collaborative, and Communication) - Yoga Dwi Arianda; Ichsan Kamal; Wawan Supriadi; Mahdiyah Mahdiyah; Iva Sarifah (Universitas Negeri Semarang, 2024)
21st century skills, often referred to as 6C, are not only learning objectives but also the foundation for creating individuals who can compete globally. In response to these needs, various innovative learning approaches have begun to be applied in the education system. One of them is Project Based Learning (PjBL). Based on these reasons, this study aims to analyze the trend of project based learning models in improving 6C skills. This study uses the Systematic Literature Review (SLR) method with the PRISMA method. Data collection was carried out by analyzing 500 related articles found on Google Scholar. After the selection process is complete, the data collected will be presented in narrative form. The results of this study underline that Project-Based Learning (PjBL) is an effective learning method to support skill development, both in academic and non-academic aspects. Although there are a number of challenges in its implementation, the advantages of PjBL in encouraging motivation, increasing engagement, and shaping student character make it a feasible approach to be implemented widely at various levels of education. The implication of this finding is the need for integration of PjBL into the education curriculum with adequate training support for educators so that this method can be applied optimally and have a positive impact on the quality of learning.